Reflecting sex, social class and race inequalities in reproduction? Study of the gender representations conveyed by 38 fertility centre websites in 8 European countries - Virginie Rozée; Anna De Bayas Sanchez; Michaela Fuller; María López-Toribio; Juan A. Ramón-Soria; Jose Miguel Carrasco; Kristien Hens; Joke Struyf; Francisco Guell; Manon Vialle (BMC, 2024)
Abstract Background Fertility centre websites are a key sources of information on medically assisted reproduction (MAR) for both infertile people and the general public. As part of a global fertility market, they are also a window to attract potential future patients. They give formal and practical information but in the way the information is displayed, they also convey social representations, and in particular, gender representation in its intersectional dimension. The objective is to analyse the sex, class and race representations regarding reproduction and parenthood that are embedded in the content of fertility centre websites in eight European countries. Methods The 5 most visible fertility centres that appeared in the first places on Internet search were selected for each country under study, except for one country which has only three fertility centres. In total, 38 fertility centre websites were considered for a thematic analysis using an iterative approach and a comprehensive perspective. Results Each centre details its services and techniques according to the legal provisions in force in its country. However, on all the websites studied, the fertility centres demonstrate a strong gendered representation. The logos generally depict women or parts of their bodies, as do the photos, which mainly show white women with light eyes. The description of the causes of infertility and the techniques offered by the centres also highlights gender differences. Sperm donation, where MAR is reserved for heterosexual couples, is included among the techniques for women with the comment that it will enable them to fulfil their dream of becoming mothers. Conclusions MAR, and through it the project of having a child and procreative work, is presented as a matter for white, cisgender and heterosexual women, thus fueling stratified reproduction and limiting reproductive justice. The research team formulated guidelines for fertility centres to encourage them to adopt a more inclusive approach in terms of sex, social class and race, so that the diversity of infertile people feel involved and welcome in these centres, to avoid misperceptions about infertility in the general population and to reinforce autonomy and justice in reproductive matters.